Identification of Interference HV Line Protection in PLGTU PT PJB Gresik Generation Unit using Method RCFA and FDT - Resti Pranandari; Misbah, Misbah,; Deny Irawan (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2021)
In the electricity generation business in Indonesia, power plants requiring to be reliable when operating and ready when needed due to network load requirements. It has been written in the performance target contract for each unit, therefore the protection system installed at the power plant must be well. The problem that occurs at the PLTGU PT PJB Gresik Generation Unit is a malfunction in the HV Line protection system that causes the generator unit to trip, thus causing questions regarding the cause of the problem that occurs. Therefore, the authors compile a thesis proposal with the title "Identification of HV Line Protection Interference at PLTGU PT PJB Gresik Generation Unit Using RCFA and FDT Methods" which can find out the source of the problem that occurs so that it does not occur repeatedly. The benefit that can take is knowing the problem cause of the HV Line protection system malfunction so that it can be done correctly and on target for future unit reliability.